Parental Reflective Functioning Among Parents with History of Childhood Abuse: A Preliminary Mixed-Method Study - Fitri, Radhiatul; Supra Wimbarti; Nita Handayani; Edilburga Wulan Septandari (UIN Sunan Kalijaga, 2025)
This preliminary study explored Parental Reflective Functioning (PRF) among parents with a history of childhood abuse. PRF, the ability to understand a child’s mental state, played a key role in breaking the cycle of intergenerational maltreatment. An explanatory sequential mixed-method design was employed, involving 10 participants in a quantitative phase and two in a follow-up qualitative phase. No significant correlation was found between childhood abuse and PRF. However, qualitative findings revealed key themes, including coping strategies, parenting outcomes and related challenges. This study provided initial insights and highlighted the need for further research with larger samples. Studi pendahuluan ini mengeksplorasi fungsi refleksi orangtua (FRO) pada orangtua dengan riwayat kekerasan di masa kanak-kanak. FRO, kemampuan untuk memahami keadaan mental anakk, berperan penting dalam memutus siklus kekerasan intergenerasi. Penelitian ini menggunakan desain mixed-method dengan pendekatan sekuensial eksplanatori, melibatkan 10 partisipan pada fase kuantitatif dan dua partisipan pada fase kualitatif lanjutan. Tidak ditemukan korelasi signifikan antara kekerasan di masa kanak-kanak dengan FRO. Namun, temuan kualitatif mengungkap tema-tema utama, termasuk strategi koping, outcome pengasuhan dan tantangan terkait. Studi ini memberikan wawasan awal dan menekankan perlunya penelitian lanjutan dengan jumlah partisipan yang lebih besar.